Engagement of public and private medical facilities in tuberculosis care in Myanmar: contributions and trends over an eight-year period - Thin Thin Nwe; Saw Saw; Le Le Win; Myo Myo Mon; Johan van Griensven; Shuisen Zhou; Palanivel Chinnakali; Safieh Shah; Saw Thein; Si Thu Aung (BMC, 2017)
Abstracts Background As part of the WHO End TB strategy, national tuberculosis (TB) programs increasingly aim to engage all private and public TB care providers. Engagement of communities, civil society organizations and public and private care provider is the second pillar of the End TB strategy. In Myanmar, this entails the public-public and public-private mix (PPM) approach. The public-public mix refers to public hospital TB services, with reporting to the national TB program (NTP). The public-private mix refers to private general practitioners providing TB services including TB diagnosis, treatment and reporting to NTP. The aim of this study was to assess whether PPM activities can be scaled-up nationally and can be sustained over time. Methods Using 2007-2014 aggregated program data, we collected information from NTP and non-NTP actors on 1) the number of TB cases detected and their relative contribution to the national case load; 2) the type of TB cases detected; 3) their treatment outcomes. Results The total number of TB cases detected per year nationally increased from 133,547 in 2007 to 142,587 in 2014. The contribution of private practitioners increased from 11% in 2007 to 18% in 2014, and from 1.8% to 4.6% for public hospitals. The NTP contribution decreased from 87% in 2007 to 77% in 2014. A similar pattern was seen in the number of new smear (+) TB cases (31% of all TB cases) and retreatment cases, which represented 7.8% of all TB cases. For new smear (+) TB cases, adverse outcomes were more common in public hospitals, with more patients dying, lost to follow up or not having their treatment outcome evaluated. Patients treated by private practitioners were more frequently lost to follow up (8%). Adverse treatment outcomes in retreatment cases were particularly common (59%) in public hospitals for various reasons, predominantly due to patients dying (26%) or not being evaluated (10%). In private clinics, treatment failure tended to be more common (8%). Conclusions The contribution of non-NTP actors to TB detection at the national level increased over time, with the largest contribution by private practitioners involved in PPM. Treatment outcomes were fair. Our findings confirm the role of PPM in national TB programs. To achieve the End TB targets, further expansion of PPM to engage all public and private medical facilities should be targeted.